IMPLEMENTASI KEBIJAKAN PERATURAN DAERAH KOTA SEMARANG NOMOR 10 TAHUN 2009 TENTANG PENYELENGGARAAN DAN RETRIBUSI PELAYANAN PEMAKAMAN JENAZAH DI KOTA SEMARANG - Setiawati, Indri; Subowo, Ari (Journal of Public Policy and Management Review, 2019)
Humans can not be separated from two important things in life, namely birth and death. Birth can be a problem if the birth rate continues to increase so that there is an increase in population. The ever increasing number of population causes the people's needs to decrease. This relates to Semarang City Regulation Number 10 of 2009 concerning the Implementation and Retribution of Burial Funeral Services in the City of Semarang, which relates to requiring housing developers to provide public or social facilities that contain a public cemetery at least 2% of the housing location that will built. The results of this study show how the implementation of the policies implemented, which are related to the provision of land locations, plots and supporting facilities for the cemetery area, and provided by developers who do not provide public burial sites